2015
DOI: 10.1021/acsami.5b02264
|View full text |Cite
|
Sign up to set email alerts
|

High Photoresponsivity and Short Photoresponse Times in Few-Layered WSe2 Transistors

Abstract: Here, we report the photoconducting response of field-effect transistors based on three atomic layers of chemical vapor transport grown WSe2 crystals mechanically exfoliated onto SiO2. We find that trilayered WSe2 field-effect transistors, built with the simplest possible architecture, can display high hole mobilities ranging from 350 cm(2)/(V s) at room temperature (saturating at a value of ∼500 cm(2)/(V s) below 50 K) displaying a strong photocurrent response, which leads to exceptionally high photoresponsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
92
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 46 publications
4
92
2
Order By: Relevance
“…[11,14,25] We used four-layer flakes for our photocurrent measurements as Pradhan et al showed that the use of few-layer TMDCs can reduce photocurrent response times while keeping photoresponsivity high. [26] Work done by Lezama et al also shows the transition of MoTe 2 to a direct band gap beginning at a flake thickness of four layers. [5] In Figure 1a, an optical microscopy image of a MoTe 2 flake of thickness from one to five layers is shown; the difference in flake thickness is…”
Section: Communicationmentioning
confidence: 90%
See 1 more Smart Citation
“…[11,14,25] We used four-layer flakes for our photocurrent measurements as Pradhan et al showed that the use of few-layer TMDCs can reduce photocurrent response times while keeping photoresponsivity high. [26] Work done by Lezama et al also shows the transition of MoTe 2 to a direct band gap beginning at a flake thickness of four layers. [5] In Figure 1a, an optical microscopy image of a MoTe 2 flake of thickness from one to five layers is shown; the difference in flake thickness is…”
Section: Communicationmentioning
confidence: 90%
“…We believe that the fast photoresponse we observe is potentially due to three reasons: the thickness of our photodetectors, the crystal quality and the sampling rate/laser rise time used in our photoresponse measurements. We used four-layer flakes in our study, and other similar thickness TMDCs devices have previously shown a fast photoresponse [26,32] whereas using monolayer flakes appears to hamper the photoresponse speed (see Table S1 of the Supporting Information for full details of flake thickness in correlation to response speeds). We also note that for the fastest (to our knowledge) reported TMDC photoresponse time reported to date, for SnS 2 devices, [33] the crystal quality was shown to play a key role in determining the speed of response.…”
Section: Communicationmentioning
confidence: 99%
“…In particular, in the case of the ReSe 2 photodetector (Figure 3 h), a sharp increase or decrease was observed at the rising and decaying edges of the temporal photoresponse curves, indicating the much faster photoswitching speed of the ReSe 2 -based device compared to the MoS 2 device showing relatively slow changes. [ 53 ] Exceptionally, when a photodetector was fabricated on tin-based chalcogenides (SnS 2 or SnSe 2 ), its rising and decaying times were very short, as much as 5-7 µs. As expected, the ReSe 2 photodetector showed much shorter rising and decaying times compared to the MoS 2 photodetector ( τ r / τ d : 0.01/0.041 s for ReSe 2 and 6.97/12.2 s for MoS 2 ).…”
Section: Communicationmentioning
confidence: 99%
“…This approach using a 1D ZnO-2D WSe 2 heterojunction paves the way for the further development of electronic/optoelectronic applications using mixed-dimensional vdW heterostructures.transition metal dichalcogenides of MoS 2 , MoTe 2 , and WSe 2 , post-transition metal dichalcogenides of SnS 2 and SnSe 2 , and black phosphorus (BP), have been synthesized; furthermore, their prototype electronic/optoelectronic applications have been demonstrated for field-effect transistors, [3][4][5][6][7][8][9] logic circuits, [8,[10][11][12][13] light-emitting diodes, [14,15] phototransistors, [16][17][18][19][20] and photodiodes. In particular, the dangling-bond-free surface of 2D materials enables integration of differently dimensioned materials into mixed-dimensional vdW heterostructures.…”
mentioning
confidence: 99%
“…To the best of our knowledge, this is the first demonstration of an optoelectronic device based on a 1D-2D hybrid vdW heterojunction. This approach using a 1D ZnO-2D WSe 2 heterojunction paves the way for the further development of electronic/optoelectronic applications using mixed-dimensional vdW heterostructures.transition metal dichalcogenides of MoS 2 , MoTe 2 , and WSe 2 , post-transition metal dichalcogenides of SnS 2 and SnSe 2 , and black phosphorus (BP), have been synthesized; furthermore, their prototype electronic/optoelectronic applications have been demonstrated for field-effect transistors, [3][4][5][6][7][8][9] logic circuits, [8,[10][11][12][13] light-emitting diodes, [14,15] phototransistors, [16][17][18][19][20] and photodiodes. [21][22][23][24] While there has been great progress in the field of 2D vdW materials, challenges have yet to be resolved for realizing their full potential:(1) implementation of high-speed operation to replace silicon or III-V compound semiconductors, (2) control of carrier type and concentration by doping, and (3) development of high quality all 2D vdW heterostructures over large areas.Recently, Jariwala et al introduced mixed-dimensional vdW heterostructures, which are a very promising strategy for overcoming the limitations of electronics based on 2D vdW materials.…”
mentioning
confidence: 99%